Instrumento de detección temprana de riesgo psicosocial, asociado a TCA - Valbuena Quiñonez, Martha Cecilia
The phenomenon of anorexia, bulimia and TCANE, non specified food conduct disease food conduct disorders, has evolved across the changes in social habits and the appearance of sociocultural factors that favor the beauty of the body as social ideal, with behavioral alterations both of ingestion and corporal image. An important tool for disorders (TCA) is prevention, since it contributes to control the factors of risk of this disease and bearing in mind that there is not a standard tool in Colombia, a psychometrict tool of 124 items was desiged to detect the psychosocial risk level associated with the development of food conduct disorders supported by a quan methodology applied to a femenine undiagnosed population sample of 640 people distributed between the city of Bogotá D.C. and Chía - Cundinamarca, who were 11 - 18 years old. Later the results were analyzed in SPSS, obtaining Cronbach’s Alfa α = .951, a pilot test, ratifying the validity and reliability of the instrument, in order to grant a probabilístic concept of level of risk to teenagers with preventive and of awareness purposes.